26th IEEE International Conference on Distributed Computing Systems (ICDCS'06)
DOI: 10.1109/icdcs.2006.46
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Multicast Routing Metrics in Wireless Mesh Networks

Abstract: The stationary nature of nodes in a mesh network has shifted the main design goal of routing protocols from maintaining connectivity between source and destination nodes to finding high-throughput paths between them. In recent years, numerous link-quality-based routing metrics have been proposed for choosing high-throughput paths for unicast protocols. In this paper we study routing metrics for high-throughput tree or mesh construction in multicast protocols. We show that there is a fundamental difference betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 28 publications
(30 reference statements)
0
44
0
Order By: Relevance
“…The major limitation of BSMR is its reliance on static detection threshold, which is independent of the channel quality and medium access collisions. Similarly, SODMRP is a secure high-throughput multicast protocol based on ODMRP and link layer metric, SPP (success probability product) [27]. SODMRP addresses packet dropping attacks by detecting the discrepancies between expected packet delivery ratio (ePDR) and perceived packet delivery ratio (pPDR).…”
Section: Related Workmentioning
confidence: 99%
“…The major limitation of BSMR is its reliance on static detection threshold, which is independent of the channel quality and medium access collisions. Similarly, SODMRP is a secure high-throughput multicast protocol based on ODMRP and link layer metric, SPP (success probability product) [27]. SODMRP addresses packet dropping attacks by detecting the discrepancies between expected packet delivery ratio (ePDR) and perceived packet delivery ratio (pPDR).…”
Section: Related Workmentioning
confidence: 99%
“…In NLR 6 protocol, they compared NLR with hop-count, [16][17][18] Expected Transmission Count (ETX), 14 Success Probability Product (SPP), 12 Load-count 4,13 and Weighted Cumulative Expected Transmission Time (WCETT-LB) 19 metric in average packet delivery ratio, average throughput, average end-to-end delay and average jitter in grid topology. The simulation results showed that the average throughput is 1.08 times the normalized value in NLR than Load-count, hopcount, ETX and SPP.…”
Section: Nlrmentioning
confidence: 99%
“…Furthermore, unicast probing of ETX is not accurate as differences between broadcast and unicast. Success Probability Product (SPP) [6] is a Routing Metric to enhance the throughput in Wireless Mesh Networks. The authors in [5] modify an energy-efficient routing metric and produce SPP to provide the probability for the destination node to receive a packet over a link.…”
Section: D) Error Rate Routing Metricmentioning
confidence: 99%
“…In this paper, we first review the performance of a list of existing routing metrics, Hop-count [11] [12] [13], ETX [9], SPP [6], Load-count [7] [8], and WCETT-LB [14] and so forth. We also describe the possible open issues remain in the current design of routing metrics in WMNs.…”
Section: Introductionmentioning
confidence: 99%